Cellular Correlates of Enhanced Anxiety Caused by Acute Treatment with the Selective Serotonin Reuptake Inhibitor Fluoxetine in Rats - Ravinder, Shilpa; Pillai, Anup G.; Chattarji, Sumantra (Frontiers in Behavioral Neuroscience, 2011)
Selective serotonin reuptake inhibitors (SSRIs) are used extensively in the treatment of depression and anxiety disorders. The therapeutic benefits of SSRIs typically require several weeks of continuous treatment. Intriguingly, according to clinical reports, symptoms of anxiety may actually increase during the early stages of treatment although more prolonged treatment alleviates affective symptoms. Consistent with earlier studies that have used animal models to capture this paradoxical effect of SSRIs, we find that rats exhibit enhanced anxiety-like behavior on the elevated plus-maze one hour after a single injection of the SSRI fluoxetine. Next we investigated the potential neural substrates underlying the acute anxiogenic effects by analyzing the morphological and physiological impact of acute fluoxetine treatment on principal neurons of the basolateral amygdala (BLA), a brain area that plays a pivotal role in fear and anxiety. Although earlier studies have shown that behavioral or genetic perturbations that are anxiogenic for rodents also increase dendritic spine-density in the BLA, we find that a single injection of fluoxetine does not cause spinogenesis on proximal apical dendritic segments on BLA principal neurons an hour later. However, at the same time point when a single dose of fluoxetine caused enhanced anxiety, it also enhanced action potential firing in BLA neurons in ex vivo slices. Consistent with this finding, in vitro bath application of fluoxetine caused higher spiking frequency and this increase in excitability was correlated with an increase in the input resistance of these neurons. Our results suggest that enhanced excitability of amygdala neurons may contribute to the increase in anxiety-like behavior observed following acute fluoxetine treatment.